The 18S ribosomal RNA m6A methyltransferase Mettl5 is required for normal walking behavior in Drosophila. (29th April 2020) - Leismann, Jessica; Spagnuolo, Mariangela; Pradhan, Mihika; Wacheul, Ludivine; Vu, Minh Anh; Musheev, Michael; Mier, Pablo; Andrade‐Navarro, Miguel A; Graille, Marc; Niehrs, Christof; Lafontaine, Denis LJ; Roignant, Jean‐Yves
Abstract: RNA modifications have recently emerged as an important layer of gene regulation. N6‐methyladenosine (m 6 A) is the most prominent modification on eukaryotic messenger RNA and has also been found on noncoding RNA, including ribosomal and small nuclear RNA. Recently, several m 6 A methyltransferases were identified, uncovering the specificity of m 6 A deposition by structurally distinct enzymes. In order to discover additional m 6 A enzymes, we performed an RNAi screen to deplete annotated orthologs of human methyltransferase‐like proteins (METTLs) in Drosophila cells and identified CG9666, the ortholog of human METTL5. We show that CG9666 is required for specific deposition of m 6 A on 18S ribosomal RNA via direct interaction with the Drosophila ortholog of human TRMT112, CG12975. Depletion of CG9666 yields a subsequent loss of the 18S rRNA m 6 A modification, which lies in the vicinity of the ribosome decoding center; however, this does not compromise rRNA maturation. Instead, a loss of CG9666‐mediated m 6 A impacts fly behavior, providing an underlying molecular mechanism for the reported human phenotype in intellectual disability. Thus, our work expands the repertoire of m 6 A methyltransferases, demonstrates the specialization of these enzymes, and further addresses the significance of ribosomal RNA modifications in gene expression and animal behavior. Synopsis: This study identifies the Mettl5 Drosophila homolog as an m 6 A 18S rRNA methyltransferase required for normal walking behavior. Drosophila Mettl5 is required for m 6 A deposition on 18S rRNA. Drosophila Mettl5 exerts its function via Trmt112. Lack of Mettl5 impacts fly behavior and orientation. Abstract : This study identifies the Mettl5 Drosophila homolog as an m 6 A 18S rRNA methyltransferase required for normal walking behavior.